Analysis of Students Questioning Skills on Science Learning Outcomes at Junior High School - Subiantoro, Wisnu Rizki; Yulinda, Ratna; Sauqina, Sauqina (Jurnal Pijar Mipa, 2025)
The questioning skill ability is essential for students to promote science learning outcomes. This study aims to analyze students' questioning skills towards cognitive science learning outcomes. There are two students' questioning skills studied, namely factual questions and amazement. This study uses a quantitative descriptive method with data collection techniques through observation, learning outcome tests, and documentation. Observations of questioning skills are observed based on four group categories, namely factual, amazement, both questions and no questions. The results of the study showed that students who actively asked questions, especially factual and amazement types of questions, had higher cognitive learning outcomes than students who did not ask questions. The group of students with factual questions and asking both questions experienced a significant increase in learning outcome scores, while the group of students who did not ask questions and students who were only surprised experienced a small increase. Based on the learning outcome scores of students in the four question groups, it is important for students to ask a lot of questions in order to increase the achievement of cognitive science learning outcomes. This study indicates that students' questioning skills are related to student learning outcomes. The more active students ask questions, and the more varied the types of questions asked, the greater the increase in student learning outcomes. The many variations of questions asked by students are the key to deepening understanding. Students can improve their learning outcomes in a deeper and more meaningful learning process by asking many questions. This study reinforces the importance of the teacher's role in encouraging students to ask more questions during the learning process by providing appropriate motivation and treatment.